Evaluasi Sistem Pengendalian Internal atas Pembelian Persediaan di Retail CV Kurnia - Sari, Kumala Linda; Widajantie , Tituk Diah (IAI Nasional Laa Roiba Bogor, 2024)
The research was carried out with the aim of finding out and evaluating the internal control system for purchasing inventory which is useful for creating effective goods management in accordance with company objectives and avoiding damage and other things that are detrimental to CV Kurnia. The method used in conducting research is a qualitative method with data analysis techniques, a qualitative descriptive analysis method by analyzing data obtained from CV Kurnia. Analysis was carried out on the internal control system for purchasing inventory and the implementation of internal control for purchasing inventory by evaluating whether the internal control of the purchasing system at CV Kurnia was running in accordance with existing theory and comparing it. CV Kurnia has problems in the process of receiving goods and distributing employee duties. Based on the results of data collection within the company, it can be seen that the biggest problem is that there are sections that have the same job desk and it is felt that they need to split members. It can be seen that there are also obstacles in other sections that require new functions to help the process of receiving goods so that the process is responsible and Validation of goods arriving according to procedures. The final result of the research carried out is that it is necessary to separate members into sections that have the same job desk so that performance can be more effective, it is also necessary to establish a new function to assist in the process of receiving goods so that responsibility and validation of incoming goods can be controlled.